Deprotonation and aggregation of Al13 under alkaline titration: A simulating study related to coagulation process. (15th September 2021) - An, Guangyu; Yue, Ye; Wang, Pin; Liu, Libing; Demissie, Hailu; Jiao, Ruyuan; Wang, Dongsheng
Highlights: OH − was consumed mainly to react with Al13 at 2.46 <  B  < 3.02. Most Al13 keep structure unchanged during the aggregation process. Al13 became unstable after deprotonation and favored to lose more protons. Deprotonated Al13 preferentially aggregated via bridged by Al monomers. Particles can promote the aggregation of Al13 by adsorption effect. Abstract: Unraveling the transformation of coagulants and their interaction with contaminants at the micro-level is vital to advancing our understanding of the coagulation mechanism. To the best of our knowledge, the coagulation effectiveness of [AlO4 Al12 (OH)24 (H2 O)12 ] 7+ (Al13 ), regarded as the dominant species in polyaluminum chloride (PACl), is highly related to its aggregation characteristic, but the detailed process of Al13 aggregation in coagulation time scale was not well studies. Here we systematically studied the deprotonation and aggregation processes of Al13 by alkaline titration to simulate the reaction in coagulation case. By reacting with OH −, Al13 can continuously lose protons regardless of pH until its positive charge was well neutralized. The initial Al13 aggregates (Al13 agg) appeared at B of 2.70 and large Al13 agg was generated by coalescence of small initial Al13 agg. Most Al13 polycations kept their main structure unchanged during aggregation and part was decomposed into monomers or oligomers. Density functional theory (DFT) results reveal that Al13 becomes unstable after deprotonation, but the aggregation of Al13 bridged by Al monomers can stabilize the polycations. Al13 needs to be hydrolyzed before interacting with colloidal particles, but particles can promote the aggregation of Al13 by weakening the repulsion force between the polymers. Strong and compact flocs can be generated induced by in-situ aggregation of Al13 in neutral and alkaline conditions. This study can provide a deep understanding about the role of Al13 agg in removing particles and instruct the development of new efficient coagulants against the various water qualities. Graphical abstract: Image, graphical abstract